THE IMPACT OF CLIMATE CHANGE ON THE RELIABILITY AND RESILIENCE OF DEFENSE ELECTRONIC SYSTEMS - Aura Purify; Dorado Sembiring (JURNAL ELEKTROSISTA, 2026)
As global climate patterns shift toward more frequent and intense extremes, the operational reliability of defense electronic systems—the core of modern military capability—faces unprecedented environmental stress. This study investigates the correlation between climate change variables and the degradation of Army electronic hardware through a systematic literature review. Analysis of data from military standards (MIL-STD-810H) and strategic climate projections reveals that rising mean temperatures, persistent humidity, and increased atmospheric salinity significantly accelerate failure modes such as thermal aging, electrochemical corrosion, and dendritic growth. The findings indicate that traditional engineering safety margins, established using static historical data, are increasingly insufficient to maintain Mean Time Between Failures (MTBF) in tropical and volatile theaters. The paper concludes that a paradigm shift in defense procurement is required, recommending the adoption of wide-bandgap (WBG) semiconductors, AI-driven Prognostics and Health Management (PHM), and revised ruggedization protocols to ensure combat readiness in an era of climate volatility.